PHARMACO-ECONOMICBENEFITS OF CORRECTION OF ANEMIA WITH CONTINUOUS ERYTHROPOIETIN RECEPTOR ACTIVATOR:HEMODIALYSIS VSHEMODIAFILTRATION - Novakivskyy, V. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Anemia is an integral component of CKD. The prescribing of erythropoiesis stimulating agents (ESA) for the treatment of anemia constitutes a significant burden on health budgets. Using of continuous erythropoietin receptor activator (CERA) and convective techniques can improve health indicators and economic results. The aim of the study was to evaluate the effects of hemodiafiltration treatment (HDF) on the pharmaco-economic efficiency of anemia treatment in comparison with haemodialysis (HD). Methods. A prospective cross-sectional study involving 40 patients with CKD stage V who receiving dialysis treatment at the LLC “Fresenius Medical Care Ukraine ” Medical center in Cherkasy city. The follow-up period was 2 years. First, data was analyzed while patients received HD over a period of twelve months. Then, the same patients were evaluated during treatment with HDF for at least another twelve months. Result. The average dose of CERA reduced from 60 mg to 44 mg per month (p = 0.002) after the transferred ofpatients to HDF treatment. There were a significantly increased the levels of Kt / V (p = 0.04) and serum albumin (p = 0.04). A higher number of patients achieved the target hemoglobin results. Conclusions. The comparison of pharmaco-economic component of anemia correction with CERA cross-sectional study demonstrates significant advantages of HDF treatment compared to HD.